A bibliometric analysis of family firm internationalization research: Current themes, theoretical roots, and ways forward. Issue 5 (October 2020) - Casprini, Elena; Dabic, Marina; Kotlar, Josip; Pucci, Tommaso
Highlights: 161 core publications are analysed through bibliometric techniques. Bibliographic coupling reveals 5 clusters (e.g. Ownership, Networks). Co-citation analysis reveals 7 clusters (e.g. Resource-Based View and Uppsala Model). An integrative framework is proposed for internationalization of family firms. Future research questions are highlighted. Abstract: This paper presents a bibliometric analysis and a systematic literature review of 161 core contributions concerning family firm internationalization. A bibliographic coupling analysis and a co-citation analysis reveal the richness of family firm internationalization research and help to organize this large body of work into five thematic clusters and seven theoretical roots. By examining the linkages between research themes and theoretical roots, we advance an integrative framework, clarifying the variety of research paths available regarding the internationalization of family firms, and identifying new and important research avenues for further developing the field.